Hot tea consumption and its interactions with alcohol and tobacco use on the risk for esophageal cancer: A population-based cohort study - Yu, C; Tang, H; Guo, Y; Bian, Z; Yang, L; Chen, Y; Tang, A; Zhou, X; Yang, X; Chen, J; Chen, Z; Lv, J; et al. (Royal College of Surgeons, 2018)
Background While the high-temperature tea consumption has been suggested as a risk factor for esophageal cancer (EC), this has not been consistently observed and whether it is independent of alcohol and tobacco exposure has not been evaluated. Objective To examine the joint association of high-temperature tea consumption and established risk factors of alcohol consumption and smoking on EC risk. Design China Kadoorie Biobank, prospective cohort study established during 2004-08. Setting Ten areas across China Participants 456,155 participants aged 30-79 years after excluding participants with cancer at baseline and those who had cut down consumption of tea, alcohol, or tobacco before baseline. Measurements The usual temperature at which tea was consumed, other tea consumption metrics, and lifestyle behaviors were self-reported once at baseline. Outcome was EC incidence until 2015. Results During a median of 9.2 years of follow-up, we documented 1,731 incident EC cases. We found that high-temperature tea consumption in combination with either alcohol consumption or smoking had a greater risk of developing EC than high-temperature tea consumption alone. Compared with participants who consumed tea less than weekly and consumed alcohol <15g per day, those daily consumers who preferred burning hot tea and consumed alcohol ≥15g had the greatest risk of developing EC (hazard ratio=5.00; 95% CI: 3.64, 6.88). Similarly, the hazard ratio (95% CI) for those who were both current smoker and daily tea consumer preferring burning hot tea was 2.03 (1.55, 2.67). Limitations Tea consumption was self-reported once at baseline, leading to the possibility of nondifferential misclassification and attenuation of the association. Conclusion Our findings highlight the importance of abstaining from high-temperature tea in excessive alcohol consumers and smokers on EC prevention.